PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN DI PT. PERKEBUNAN NUSANTARA IV JAMBI - sonia agustina; Johandri Iqbal; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2025)
This study aims to find out the extent of the influence of accounting information systems and internal control on. The population of this study is all employees at PT. Nusantara IV Jambi Plantation. This type of research is quantitative. The technique used in the data collection of this study is Purposive Sampling, the number of samples used is 35 samples consisting of employees who are in charge of finance and internal control. Data collection is by sharing several questionnaire statements. The measuring tool used in this analysis is the SPSS version 30.0 program. The results of this analysis are that the Accounting Information System variable partially does not have a significant effect on the Quality of Financial Statements, and the Internal Control variable partially has a positive and significant effect on the Quality of Financial Statements. Meanwhile, the Accounting Information System and Internal Control variables simultaneously have a positive and significant effect on the Quality of Financial Statements.